BRIDGING THE GAP: STRATEGIES FOR IMPLEMENTING STUNTING PREVENTION POLICIES IN KENDARI CITY - Sarinah Sarinah (Universitas Sultan Ageng Tirtayasa, 2025)
This research aims to identify gaps in the implementation of stunting prevention policies in Kendari City. The study employs a qualitative research approach with a descriptive method, utilizing data collection techniques such as in-depth interviews, participatory observation, and document analysis. The research subjects include officials from the Kendari City Health Office, healthcare workers from community health centers, and cadres from the Integrated Family Planning and Health Service Posts involved in the stunting prevention program. Data analysis follows the stages of data reduction, data presentation, and conclusion drawing with verification. The findings reveal that stunting prevention policy strategies in Kendari City encompass corporate strategy, program strategy, resource support strategy, and institutional strategy. Despite the program's implementation, several challenges persist, including suboptimal cross-sector coordination, limited access to healthcare services, and socio-economic factors influencing children's nutritional intake. This study highlights the need for stronger stakeholder synergy, enhanced community-based education, and optimized resource allocation to improve policy effectiveness. The study's recommendations include expanding program outreach, implementing economic interventions for families at risk of stunting, and strengthening technology-based recording and reporting systems to ensure the policy is implemented effectively and sustainably